Scraping and moxibustion therapy and nursing of a breast cancer patient with COVID-19 in convalescence (1例乳腺癌患者新型冠状病毒感染恢复期应用刮灸疗法的护理体会) - YAN Kang (严康); LIU Shuhong (刘书红); ZHAO Yanan (赵亚楠) (中西医结合护理)
To explore effect of scraping and moxibustion therapy for a breast cancer patient with COVID-19 in convalescence. On the basis of Traditional Chinese Medicine syndrome differentiation, the Du meridian (Dazhui) and the bladder meridian (Feishu, Pishu) of the patient were treated with scraping and moxibustion once a day. The comprehensive nursing interventions including daily care, nutrition guidance, symptomatic care and emotion care were carried out during the treatment. Scraping and moxibustion therapy can effectively alleviate cough, fatigue and other symptoms of COVID-19 in convalescence. (本文总结1例乳腺癌患者新型冠状病毒感染恢复期应用刮灸疗法的效果和护理经验。基于患者辨证分型, 选取督脉(大椎)和膀胱经(肺俞、脾俞)进行刮灸, 同时配合生活起居管理、饮食指导、症状护理、情志护理等常规护理, 有效缓解患者咳嗽、咳痰、乏力、腹胀等多种症状。)